Raman spectroscopy analysis of number of layers in mass-produced graphene flakes. (May 2020) - Silva, Diego L.; Campos, João Luiz E.; Fernandes, Thales F.D.; Rocha, Jeronimo N.; Machado, Lucas R.P.; Soares, Eder M.; Miquita, Douglas R.; Miranda, Hudson; Rabelo, Cassiano; Vilela Neto, Omar P.; Jorio, Ado; Cançado, Luiz Gustavo
Abstract: A metrological framework for statistical analysis of number of layers and stacking order in mass-produced graphene using Raman spectroscopy is presented. The method is based on two complementary protocols, denominated by 2D and G. The 2D–protocol is based on the parameterized principal component analysis of the two-phonon 2D band, and it measures interlayer coupling. A neural-network algorithm for spectral denoising was also developed to improve the outcome. The G–protocol explores the intensity of the bond-stretching G band, and provides information about the number of layers. The method is suitable for automated statistical analysis of heterogeneous graphene-based systems with relatively low computational cost, as shown here for graphene flakes prepared by the liquid-phase exfoliation of graphite. Graphical abstract: Image 1